Remediation and Counter-Hegemony of Gender Dichotomy in Indonesian Family: Multimodal Discourse Analysis of Two Kecap Advertisements - Justito Adiprasetio; Annissa Winda Larasati (Center for Southeast Asian Social Studies (CESASS), 2019)
Until now hegemonic gender dichotomyin Indonesia has worked in various spheres of human life, in various social roles, even in the smallest unitof social organizations: family. The dichotomy was caused by the ideology of